The 1979 Constitution and Labor Law - Blancas Bustamante, Carlos (1982)
The 1979 Constitution introduced innovations and improvements in the recognition of rights. One of these cases is the relevance with which this Magna Carta addresses labour law in the Peruvian legal system. To that extent, it can be observed that the Peruvian Constitution of 1979 not only highlights the fundamental character of this right, but also conceives work as a social and economic fact in the country. Consequently, this constitutional text is classified as a manifestation of social constitutionalism that seeks to enshrine in its pages the guiding principles of labour law. This situation has allowed work to be established as a means of human fulfilment and as the main source of wealth for the State. However, while there is no doubt that this constitution represents a significant advance for labour law, it should be mentioned that having recognised the foundations of social constitutionalism also represents a problem between this right and the consolidation of a capitalist economy. In this context, this article details the way in which this Constitution has consolidated labour law, the advances that exist on the subject in the constitutional framework and the details that are involved.